Canadian journal of Latin American and Caribbean studies = Revue canadienne des études latino-américaines et caraïbes (Canadian Association for Latin American and Caribbean Studies, 1984)
Contribuye a la promoción de los conocimientos sobre América Latina y el Caribe en Canadá y en todo el mundo